Nonlinear Black Phosphorus for Ultrafast Optical Switching - Uddin, Siam; Debnath, Pulak C.; Park, Kichul; Song, Yong-Won (Nature Publishing Group, 2017)
The outstanding electronic and optical properties of black phosphorus (BP) in a two-dimensional (2D) but unique single-layer puckered structure have opened intense research interest ranging from fundamental physics to nanoscale applications covering the electronic and optical domains. The direct and controllable electronic bandgap facilitating wide range of tunable optical response coupled with high anisotropic in-plane properties made BP a promising nonlinear optical material for broadband optical applications. Here, we investigate ultrafast optical switching relying on the optical nonlinearity of BP. Wavelength conversion for modulated signals whose frequency reaches up to 20 GHz is realized by four-wave-mixing (FWM) with BP-deposited D-shaped fiber. In the successful demonstration of the FWM based wavelength conversion, performance parameter has been increased up to similar to 33% after employing BP in the device. It verifies that BP is able to perform efficient optical switching in the evanescent field interaction regime at very high speed. Our results might suggest that BP-based ultrafast photonics devices could be potentially developed for broadband applications.